Rediscovery of Phrynopus peruanus Peters 1874 (Amphibia, Anura, Leptodactylidae) - Lehr, Edgar (Zootaxa, 2007)
Phrynopus peruanus, the type species of the genus, was described by Peters in 1874 based on three specimens from “Maraynioc in Peru”. In 1975, Lynch redescribed the species based on two preserved females, but skin texture, male characters, coloration in life, and precise information on the type locality and natural history remained unknown or uncertain. In December 2005, four specimens of P. peruanus were found at the Puna of Maraynioc at 3825 m a.s.l. in the Vitoc Valley (Departamento de Junín). Males were calling from inside the bunched Peruvian Feather Grass (Stipa icchu). Coloration in life and morphology of males and females are described along with observations on their habitat and ecology.